Petugas Pastoral Menumbuh Kembangkan Kepribadian Sekami Di Stasi St. Yohanes Paroki St. Fidelis Pulau-Pulau Batu - Mawarni Gea; Sergius Lay; Hermina Sarumaha (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research departs from the author's concern about the reality that is happening to SEKAMI children at St. John, St. Fidelis Rock Islands, where they still cannot be SEMI Catholic children as expected by the Church. The main problem discussed is that SEKAMI assistants, especially pastoral officers, have not succeeded in developing the personality of SEKAMI children, based on the methods and efforts they have tried and applied. In preparing this thesis, the authors use qualitative research methods. Qualitative research is research that describes phenomena, events, and social activities that occur scientifically. The qualitative approach method is an approach by looking at the object of study as a system, meaning that the object of study is seen as a unit consisting of related elements. The Church sees the importance of education and personality formation from an early age, so that later they can grow into generations that are useful for the nation and the Church. Therefore, pastoral officers should play a big role and try their best to be able to accompany and develop the personality of SEKAMI's children according to what the Church expects.